1983
DOI: 10.1159/000123469
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum Corticosterone in Rats by Dopamine Agonists Related in Structure to Pergolide

Abstract: Two chemical analogs of pergolide were examined to test further the idea that pergolide elevates serum corticosterone concentration in rats by activation of brain dopaminergic receptors. LY116467, which contains an N-methyl substituent in place of the N-n-propyl substituent in pergolide, was less potent than pergolide in lowering brain levels of 3,4-dihydroxyphenylacetic acid (Dopac), the metabolite of dopamine. LY 116467 increased serum corticosterone concentration in rats at a dose of 3 mg/kg (a higher dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…The refore, the D-2 stimulation in vivo probably involves the se cretion of hypothalamic CRF [32]. In support of a central D-2 mechanism are previous findings that the peripherally acting D-2 antagonist, domperidone, did not block the in crease in serum corticosterone evoked by LY141865 [9], In the present study, central administration of sulpiride inhi bited LY141865-evoked ip-END release ( fig. 5), whereas pe ripherally administered sulpiride did not [Farah and Mueller, unpubl.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The refore, the D-2 stimulation in vivo probably involves the se cretion of hypothalamic CRF [32]. In support of a central D-2 mechanism are previous findings that the peripherally acting D-2 antagonist, domperidone, did not block the in crease in serum corticosterone evoked by LY141865 [9], In the present study, central administration of sulpiride inhi bited LY141865-evoked ip-END release ( fig. 5), whereas pe ripherally administered sulpiride did not [Farah and Mueller, unpubl.…”
Section: Discussionsupporting
confidence: 82%
“…Holland et al [12] observed that both the dopa mine receptor agonist, apomorphine, and the dopamine pre cursor, L-dihydroxyphenylalanine, stimulated the release of adrenal glucocorticoids in conscious dogs. More recently, Fuller et al [8,9] reported that dopaminergic agonists elevate serum corticosterone levels in rats. These findings have been extended by the observations that the dopamine agonist, ap omorphine, increases circulating levels of ACTH and (1-LPH in rats [6,15].…”
mentioning
confidence: 99%
“…Reduced D2-receptor sensitivity was also observed with regard to corticosterone secretion. Both systemic and intraventricular administration of quinpirole stimulates plasma corticosterone secretion (Borowsky and Kuhn, 1992;Foreman et al, 1989;Fuller et al, 1983). More recent work has demonstrated that the stimulatory effects of dopamine agonists on corticosterone secretion are mediated by activation within the ventral striatum (Ikemoto and Goeders, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The current study also measured plasma corticosterone immediately after the completion of behavioral testing to determine whether any of the effects on PPI observed in the postpartum females were due to alterations in corticosterone secretion in response to the testing conditions as lactating females have been found to be stress hyporesponsive under some conditions (Lightman and Young, 1989). Moreover, as D2-agonists have been found to stimulate corticosterone secretion (Borowsky and Kuhn, 1992;Foreman et al, 1989;Fuller et al, 1983) via their effects within the ventral striatum (Ikemoto and Goeders, 1998), quinpirole-stimulated corticosterone secretion served as yet another measure of D2 receptor sensitivity within the forebrain dopamine system. Finally, plasma estradiol and progesterone levels were determined in all subjects in an attempt to correlate behavioral and neurochemical changes with postpartum shifts in hormone levels.…”
Section: Introductionmentioning
confidence: 88%
“…This was finally achieved using administration of protamine sulfate, a heparin antagonist. We decided to study ACTH release as the importance of the pituitary-adrenocortical axis for the control of BBB func tion had been demonstrated [25] and as there are still man\ doubts on ACTH regulation by peripheral substances known stimulatory role of central, but not peripheral, dopa mine receptors in the control of ACTH release [9,10,17] was used to show that otherwise ineffective circulating substances can modify neuroendocrine regulations if a tran sient, reversible increase in BBB permeability occurs.…”
mentioning
confidence: 99%